Carbon-coated iron-based composite phosphate positive electrode material as well as preparation method and application thereof

Through the preparation method of carbon-coated iron-based composite phosphate positive electrode material, the problem of low conductivity of the positive electrode material of polyanionic sodium ion battery is solved, and the stable preparation and cycle stability of high-performance materials are achieved, which is suitable for industrial production. And improves the safety and economicality of the battery.

CN119218956APending Publication Date: 2024-12-31HUNAN NANENG TIMES TECH DEV CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311774110.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Polyanionic sodium ion battery positive electrode materials have problems with low conductivity and lack of stable and large-scale preparation methods for high-performance materials.

Method used

Using the preparation method of carbon-coated iron-based composite phosphate positive electrode material, through wet grinding, spray drying and high-temperature sintering steps, complexing agent is used to mix with the iron source atomic level to form conductive carbon coated on the surface of the material to enhance electrons and ions. Conductivity.

Benefits of technology

The preparation of high-performance composite phosphate positive electrode material is realized, which improves the circulation stability and specific capacity of the material, simplifies the preparation process, is suitable for industrial production, and improves the safety and economicality of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218956A_ABST
    Figure CN119218956A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and particularly relates to a carbon-coated iron-based composite phosphate positive electrode material as well as a preparation method and application thereof. The preparation method comprises the following steps: performing wet grinding on iron salt, M salt, a sodium source, a phosphorus source, a complexing agent and a solvent according to a stoichiometric ratio to obtain slurry A; carrying out spray drying on the slurry A to obtain solid powder B; pre-sintering the solid powder B in an inert atmosphere to obtain a precursor C, grinding the precursor C into powder, compacting the powder, sintering the powder at a high temperature in the inert atmosphere, and crushing the powder to obtain the carbon-coated iron-based composite phosphate positive electrode material. Wherein the chemical formula of the iron-based composite phosphate positive electrode material is Na4 [FexM1-x] 3 [PO4] 2P2O7, M is one or more of Ni, Co, Mn, Mg, Ti, Zn and Cu, and x is more than 0 and less than 1. The prepared positive electrode material is uniform in element distribution, excellent in cycling stability and high in specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a carbon-coated iron-based composite phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] Due to the shortage, high cost and uneven distribution of lithium resources, while sodium resources are abundant, easy to obtain and low in cost, sodium-ion battery technology has developed rapidly, and the industrialization process in the fields of energy storage and small power is also advancing rapidly. The positive electrode material is the core component of the battery. At present, the positive electrode materials of sodium-ion batteries can be divided into layered oxides, Prussian blue and polyanions. Among them, polyanion compounds have stable structures, high cycle life, high thermal stability and high operating voltage, making them the most suitable route for long-term energy storage.

[0003] Polyanionic compounds have a three-dimensional network structure, which is composed of transition metal ion polyhedrons and polyanions. The chemical formula is Na x M y (X a O b ) z Z w , where M is one or more of Fe, V, Mn, Ti, etc., X is Si, P, S, etc., and Z is OH-, F-, etc. Compared with layered materials, the advantages of polyanionic materials are as follows: ① Since polyanions stabilize the material structure, they have higher electrochemical stability; ② Si, S, P and other atoms form MOX bonds with transition metals and oxygen atoms, which can weaken the MO bonds and increase the reaction potential of the material; ③ Since there are many combinations of polyanions and transition metal ions, the reaction potential of the material is easy to adjust. However, due to the special structure of polyanionic compounds, the valence electrons of the anion and cation groups in the material are separated, resulting in the common problem of low conductivity in polyanionic materials. At the same time, since polyanionic materials are in the research and development stage, there is a lack of stable and large-scale preparation methods for high-performance materials. Summary of the invention

[0004] In order to overcome the problems in the prior art, the present invention provides a carbon-coated iron-based composite phosphate positive electrode material and a preparation method thereof, a positive electrode plate and a sodium ion battery. The prepared positive electrode material has uniform element distribution, excellent cycle stability and high specific capacity.

[0005] In an embodiment of the present invention, the present invention provides a method for preparing a carbon-coated iron-based composite phosphate positive electrode material, comprising the following steps:

[0006] S1. Wet-grinding iron salt, M salt, sodium source, phosphorus source, complexing agent and solvent in a stoichiometric ratio in a sand mill to obtain slurry A;

[0007] S2, spray drying the slurry A to obtain solid powder B;

[0008] S3, pre-sintering the solid powder B in an inert atmosphere to obtain a precursor C, grinding the precursor C into powder and then compacting it, and sintering it at a high temperature in an inert atmosphere, and after crushing, obtaining a carbon-coated iron-based composite phosphate positive electrode material; wherein the chemical formula of the iron-based composite phosphate positive electrode material is: Na4[Fe x M 1-x ]3[PO4]2P2O7, wherein M is one or more of Ni, Co, Mn, Mg, Ti, Zn, Cu, and 0<x<1.

[0009] In one embodiment, the complexing agent is one or more of citric acid, ethylenediaminetetraacetic acid, nitrilotriacetic acid, oxalic acid, glucose or sucrose.

[0010] In one of the embodiments, in the iron-based composite phosphate positive electrode material, the molar ratio of (Fe+M):Na:P is 3:4:4; the molar ratio of (Fe+M) to the chelating agent in the iron-based composite phosphate positive electrode material is 1:(1-5).

[0011] In one embodiment, in step S1, the M salt is one or more of soluble oxalates, acetates, nitrates, etc. containing M; the sodium source includes one or more of sodium phosphate, sodium pyrophosphate, disodium dihydrogen pyrophosphate, sodium carbonate, sodium hydroxide, sodium acetate, sodium nitrate, sodium formate and sodium iodide; the phosphorus source includes one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, pyrophosphoric acid, sodium pyrophosphate; the solvent is one or more of deionized water, methanol, ethanol, butyric acid, octanol, glycol, isopropanol, acetone, lauryl alcohol, and stearic acid.

[0012] In one embodiment, in step S1, the solid content of the slurry A is 10% to 60%.

[0013] In one embodiment, in step S2, the inlet air temperature of the spray drying process is 200-300°C, and the outlet air temperature of the spray drying process is 60-120°C.

[0014] In one embodiment, in step S3, the pre-sintering is carried out at a heating rate of 1-10°C / min from room temperature to 200-400°C, and the pre-sintering is carried out for 2-10 hours; the high-temperature sintering is carried out at a heating rate of 1-10°C / min from room temperature to 450-650°C, and the sintering time is 4-12 hours.

[0015] Based on the same technical concept, the present invention also provides a carbon-coated iron-based composite phosphate positive electrode material prepared by the preparation method of the above-mentioned carbon-coated iron-based composite phosphate positive electrode material.

[0016] Based on the same technical concept, the present invention also provides a positive electrode plate, which includes a current collector and an active layer located on the surface of the current collector, and the active layer includes the above-mentioned carbon-coated iron-based composite phosphate positive electrode material.

[0017] Based on the same technical concept, the present invention also provides a sodium ion battery, which includes the above-mentioned positive electrode plate.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The preparation method of the present invention can stably and massively prepare high-performance carbon-coated iron-based composite phosphate (composite polyanion) positive electrode materials, and the complexing agent, iron source and M source are mixed at the atomic level by the wet grinding process of a sand mill. At the same time, the particle size of the material can be strictly controlled during the wet grinding process, thereby shortening the Na + The diffusion distance of the complexing agent is shortened, and the complexing agent is decomposed in an inert atmosphere to generate conductive carbon coated on the surface of the material, which greatly improves the electronic conductivity of the material. This method improves the ionic conductivity and electronic conductivity of the material at the same time, and realizes the preparation of high-performance composite phosphate positive electrode materials. In the voltage range of 1.7-4.3V, the discharge specific capacity of the material at a current rate of 0.1C can reach 108.72mAh g -1 .

[0020] (2) The preparation method of the carbon-coated iron-based composite phosphate (composite polyanion) positive electrode material of the present invention includes the steps of wet grinding, spray drying and high-temperature sintering. The raw materials are easily available, the synthesis method is simple and easy to operate, the synthesis cycle is short, and it is easy to realize industrial production; and the battery prepared using the positive electrode material is safe, effective, economical and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 This is a SEM image of the carbon-coated iron-based composite phosphate positive electrode material provided by the present invention;

[0023] Figure 2This is an EDS surface scan of the carbon-coated iron-based composite phosphate positive electrode material prepared in Example 1 of the present invention; wherein (a) is the distribution of the Na element in the material, (b) is the distribution of the Fe element in the material, (c) is the distribution of the Mn element in the material, and (d) is the distribution of the P element in the material;

[0024] Figure 3 This is a thermogravimetric curve of the carbon-coated iron-based composite phosphate positive electrode material prepared in Example 1 of the present invention;

[0025] Figure 4 This is the XRD pattern of the carbon-coated iron-based composite phosphate positive electrode material prepared in Example 1 of the present invention;

[0026] Figure 5 This is a charge and discharge curve diagram of the carbon-coated iron-based composite phosphate positive electrode material prepared in Example 1 of the present invention at a voltage range of 1.7-4.3V and a current rate of 0.1C. DETAILED DESCRIPTION

[0027] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0028] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0029] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0030] In order to improve the cycle stability and specific capacity of the positive electrode material of the sodium ion battery, the inventor of the present application proposes a method for preparing a carbon-coated iron-based composite phosphate positive electrode material, comprising the following steps:

[0031] S1. Wet-grinding iron salt, M salt, sodium source, phosphorus source, complexing agent and solvent in a stoichiometric ratio in a sand mill to obtain slurry A;

[0032] S2, spray drying the slurry A to obtain solid powder B;

[0033] S3, pre-sintering the solid powder B in an inert atmosphere to obtain a precursor C, grinding the precursor C into powder and then compacting it, and sintering it at a high temperature in an inert atmosphere, and after crushing, obtaining a carbon-coated iron-based composite phosphate positive electrode material; wherein the chemical formula of the iron-based composite phosphate positive electrode material is: Na4[Fe x M1-x ]3[PO4]2P2O7, wherein M is one or more of Ni, Co, Mn, Mg, Ti, Zn, Cu, and 0<x<1.

[0034] In the present invention, the preparation method of the present invention utilizes a high-speed wet grinding process to mix the raw materials uniformly, and utilizes a complexing agent to complex with metal ions to achieve uniform mixing of the raw materials at the atomic level, and then obtains a precursor powder by spray drying, and then undergoes two-step calcination under an inert atmosphere, and utilizes phosphate deoxygenation under a high temperature environment to obtain an iron-based composite phosphate positive electrode material. The particle size is reduced by the pulverization process, shortening the ion transmission distance, and the complexing agent is used to decompose at high temperature to form a carbon coating to improve the electronic conductivity of the material. The discharge capacity of the material is improved by particle size control and carbon coating synergistic strategy, and the controllable preparation of high-performance iron-based composite phosphate positive electrode materials is achieved.

[0035] As an optional embodiment, the complexing agent is one or more of citric acid, ethylenediaminetetraacetic acid, nitrilotriacetic acid, oxalic acid, glucose or sucrose.

[0036] In the present invention, the role of the complexing agent is to react with the iron source and the M source during the wet grinding process, so that the raw materials are mixed at the atomic level.

[0037] As an optional embodiment, in the iron-based composite phosphate positive electrode material, the molar ratio of (Fe+M):Na:P is 3:4:4; the molar ratio of (Fe+M) to the complexing agent in the iron-based composite phosphate positive electrode material is 1:(1-5).

[0038] In the present invention, the purpose of adding M salt is to adjust the reaction potential of the material through a combination of multiple transition metal ions, so that the material exhibits a higher energy density. However, the content of the added M salt cannot be too high, because too high a content will increase the cost, and too high a content may cause uneven mixing of the materials, forming impurities and causing the performance of the materials to deteriorate.

[0039] As an optional embodiment, in step S1, the M salt is one or more of soluble oxalates, acetates, nitrates, etc. containing M; the sodium source includes one or more of sodium phosphate, sodium pyrophosphate, disodium dihydrogen pyrophosphate, sodium carbonate, sodium hydroxide, sodium acetate, sodium nitrate, sodium formate and sodium iodide; the phosphorus source includes one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, pyrophosphoric acid, sodium pyrophosphate; the solvent is one or more of deionized water, methanol, ethanol, butyric acid, octanol, glycol, isopropanol, acetone, lauryl alcohol, and stearic acid.

[0040] In the present invention, the role of the solvent is to provide a liquid environment to ensure that the raw materials are mixed more evenly.

[0041] As an optional implementation, in step S1, the solid content of the slurry A is 10% to 60%.

[0042] In the present invention, if the solid content is lower (lower than 10%), the production capacity of the material will decrease, and if the solid content is too high (higher than 60%), the mixing system will not be able to present a good liquid environment, resulting in the inability to mix the raw materials evenly.

[0043] As an optional embodiment, in step S2, the inlet air temperature of the spray drying process is 200-300°C, and the outlet air temperature of the spray drying process is 60-120°C.

[0044] As an optional embodiment, in step S3, the pre-sintering is carried out at a heating rate of 1-10°C / min from room temperature to 200-400°C, and the pre-sintering is carried out for 2-10 hours; the high-temperature sintering is carried out at a heating rate of 1-10°C / min from room temperature to 450-650°C, and the sintering time is 4-12 hours.

[0045] In the present invention, the complexing agent is first decomposed at 200-400°C to remove moisture and carbon dioxide in the complexing agent, and then the phosphate is deoxygenated to generate pyrophosphate at 450-650°C, while the crystallinity is increased, and finally a carbon-coated iron-based composite phosphate positive electrode material with good crystallinity is obtained.

[0046] The embodiments of the present application also provide a carbon-coated iron-based composite phosphate positive electrode material prepared by any of the above preparation methods.

[0047] In the present invention, the particles of the carbon-coated iron-based composite phosphate positive electrode material are evenly dispersed, with a particle size of 100nm to 2μm, and the carbon content in the carbon-coated iron-based composite phosphate positive electrode material is 0.1% to 15%.

[0048] The embodiment of the present application also provides a positive electrode sheet, which includes a current collector and an active layer located on the surface of the current collector, wherein the active layer includes the carbon-coated iron-based composite phosphate positive electrode material. In addition, the above-mentioned electrode sheets can also be assembled to obtain a sodium battery with excellent performance.

[0049] The above introduces the specific implementation methods of the present application. In order to objectively illustrate the technical effects produced by the present application, the following examples and comparative examples will be used for description.

[0050] Example 1

[0051] A method for preparing a carbon-coated iron-based composite phosphate positive electrode material comprises the following steps:

[0052] (1) FeC2O4, MnC2O4, Na2P2O7, and NH4H2PO4 were added to an ethanol solution at a molar ratio of 2.85:0.15:2:2, and citric acid was added at a molar ratio of citric acid: (FeC2O4 + MnC2O4) of 1:1, and the solid content was controlled to be 40%. The mixture was ground in a sand mill and the final grinding particle size D50 was controlled to be 0.5 μm to obtain a precursor slurry.

[0053] (2) The precursor obtained in step (1) is spray-dried, and the air inlet temperature is controlled at 150° C. and the air outlet temperature is controlled at 80° C. to obtain a precursor powder.

[0054] (3) The precursor powder of step (2) is heated to 350° C. at 3° C. / min in a nitrogen atmosphere, pre-sintered for 5 h, and then heated to 500° C. and sintered for 6 h to obtain a carbon-coated iron-based composite phosphate positive electrode material; wherein the chemical formula of the iron-based composite phosphate positive electrode material is Na4[Fe 2.85 Mn 0.15 ]3[PO4]2P2O7.

[0055] Example 2

[0056] A method for preparing a carbon-coated iron-based composite phosphate positive electrode material comprises the following steps:

[0057] (1) FeC2O4, MnC2O4, Na2P2O7, and NH4H2PO4 were added to an ethanol solution at a molar ratio of 1.5:1.5:2:2, and citric acid was added at a molar ratio of citric acid: (FeC2O4 + MnC2O4) of 1:1, and the solid content was controlled to be 40%. The mixture was ground in a sand mill and the final grinding particle size D50 was controlled to be 0.5 μm to obtain a precursor slurry.

[0058] (2) The precursor obtained in step (1) is spray-dried, and the air inlet temperature is controlled at 150° C. and the air outlet temperature is controlled at 80° C. to obtain a precursor powder.

[0059] (3) The precursor powder of step (2) is heated to 350° C. at 3° C. / min in a nitrogen atmosphere, pre-sintered for 5 h, and then heated to 500° C. and sintered for 6 h to obtain a carbon-coated iron-based composite phosphate positive electrode material; wherein the chemical formula of the iron-based composite phosphate positive electrode material is Na4[Fe 1.5 Mn 1.5 ]3[PO4]2P2O7.

[0060] Example 3

[0061] A method for preparing a carbon-coated iron-based composite phosphate positive electrode material comprises the following steps:

[0062] (1) FeC2O4, MnC2O4, Na2P2O7, and NH4H2PO4 were added to an ethanol solution at a molar ratio of 2.85:0.15:2:2, and citric acid was added at a molar ratio of citric acid: (FeC2O4 + MnC2O4) of 1:1, and the solid content was controlled to be 60%. The mixture was ground in a sand mill and the final grinding particle size D50 was controlled to be 1 μm to obtain a precursor slurry.

[0063] (2) The precursor obtained in step (1) is spray-dried, and the air inlet temperature is controlled at 150° C. and the air outlet temperature is controlled at 80° C. to obtain a precursor powder.

[0064] (3) The precursor powder of step (2) is heated to 350° C. at 3° C. / min in a nitrogen atmosphere, pre-sintered for 5 h, and then heated to 500° C. and sintered for 6 h to obtain a carbon-coated iron-based composite phosphate positive electrode material; wherein the chemical formula of the iron-based composite phosphate positive electrode material is Na4[Fe 2.85 Mn 0.15 ]3[PO4]2P2O7.

[0065] Example 4

[0066] A method for preparing a carbon-coated iron-based composite phosphate positive electrode material comprises the following steps:

[0067] (1) FeC2O4, MnC2O4, Na2P2O7, and NH4H2PO4 were added to a pure water solution at a molar ratio of 2.85:0.15:2:2, and then citric acid was added at a molar ratio of citric acid: (FeC2O4 + MnC2O4) of 1:1, and the solid content was controlled to be 40%. The mixture was ground in a sand mill and the final grinding particle size D50 was controlled to be 0.5 μm to obtain a precursor slurry.

[0068] (2) The precursor obtained in step (1) is spray-dried, and the air inlet temperature is controlled at 200° C. and the air outlet temperature is controlled at 100° C. to obtain a precursor powder.

[0069] (3) The precursor powder of step (2) is heated to 300° C. at 3° C. / min in a nitrogen atmosphere, pre-sintered for 5 h, and then heated to 450° C. and sintered for 6 h to obtain a carbon-coated iron-based composite phosphate positive electrode material; wherein the chemical formula of the iron-based composite phosphate positive electrode material is Na4[Fe 2.85 Mn 0.15 ]3[PO4]2P2O7.

[0070] Comparative Example 1

[0071] A method for preparing a carbon-coated sodium iron pyrophosphate positive electrode comprises the following steps:

[0072] (1) FeC2O4, Na2P2O7, and NH4H2PO4 are added to a pure water solution at a molar ratio of 3:2:2, and then citric acid is added at a molar ratio of citric acid:FeC2O4 of 1:1, and the solid content is controlled to be 40%. The mixture is ground in a sand mill and the final grinding particle size D50 is controlled to be 0.5 μm to obtain a precursor slurry.

[0073] (2) The precursor obtained in step (1) is spray-dried, and the air inlet temperature is controlled at 200° C. and the air outlet temperature is controlled at 100° C. to obtain a precursor powder.

[0074] (3) The precursor powder of step (2) is heated to 300° C. at 3° C. / min under a nitrogen atmosphere, pre-fired for 5 h, and then heated to 450° C. and sintered for 6 h to obtain a carbon-coated sodium iron pyrophosphate positive electrode material; wherein the chemical formula of the sodium iron pyrophosphate positive electrode material is Na4Fe3[PO4]2P2O7.

[0075] Comparative Example 2

[0076] A method for preparing a carbon-coated iron-based phosphate positive electrode comprises the following steps:

[0077] (1) FeC2O4, MnC2O4, Na2P2O7, and NH4H2PO4 were added to a pure water solution at a molar ratio of 2.85:0.15:2:2, and then citric acid was added at a molar ratio of citric acid: (FeC2O4 + MnC2O4) of 1:1, and the solid content was controlled to be 40%. The mixture was ground in a sand mill and the final grinding particle size D50 was controlled to be 0.5 μm to obtain a precursor slurry.

[0078] (2) The precursor obtained in step (1) is spray-dried, and the air inlet temperature is controlled at 200° C. and the air outlet temperature is controlled at 100° C. to obtain a precursor powder.

[0079] (3) The precursor powder of step (2) is heated to 300° C. at 3° C. / min in a nitrogen atmosphere, pre-sintered for 5 h, and then heated to 700° C. and sintered for 6 h to obtain a carbon-coated iron-based phosphate positive electrode material; wherein the chemical formula of the iron-based phosphate positive electrode material is Na3[Fe 2.85 Mn 0.15 ]3[PO4]3.

[0080] Spectral analysis

[0081] The carbon-coated iron-based composite phosphate positive electrode material obtained in the example was subjected to SEM, EDS, and XRD spectrum analysis. Taking the positive electrode material obtained in Example 1 as an example, Figure 1 This is a SEM image of the carbon-coated iron-based composite phosphate positive electrode material obtained in Example 1. Figure 1 From the SEM image, it can be seen that the particle size of the material is about 0.8 μm; Figure 2 This is the EDS spectrum of the carbon-coated iron-based composite phosphate positive electrode material obtained in Example 1. Figure 2 From the EDS spectrum, we can see that Na, Fe, Mn and P elements are evenly distributed in the material, indicating that Na4[Fe 2.85 Mn 0.15 ]3[PO4]2P2O7 cathode material; Figure 4 is the XRD pattern of the carbon-coated iron-based composite phosphate positive electrode material obtained in Example 1. Figure 4 It can be seen that the material has a good crystal structure, high purity and no impurities.

[0082] Thermogravimetric analysis

[0083] The carbon-coated iron-based composite phosphate positive electrode material obtained in the example was subjected to thermogravimetric analysis. Taking the positive electrode material obtained in Example 1 as an example, Figure 3 is a thermogravimetric curve of the carbon-coated iron-based composite phosphate positive electrode material obtained in Example 1, Figure 3 It can be seen that the carbon content in the carbon-coated iron-based composite phosphate positive electrode material obtained in Example 1 is about 1%.

[0084] Electrical performance analysis

[0085] Battery assembly: Weigh 0.2000g of the positive electrode material prepared in the examples and comparative examples, add 0.0250g of conductive carbon black as a conductive agent and 0.0250g of PVDF (polyvinylidene fluoride) as a binder, mix well and apply on aluminum foil to make a positive electrode sheet, in a vacuum glove box, use a metal sodium sheet as the negative electrode, a Whatman GF / D glass fiber separator as the battery separator, and an electrolyte of 1mol / L NaClO4 (EC:DMC=1:1 (volume ratio) + 5% FEC), and assemble into a CR2025 button cell. Electrochemical performance tests were carried out in the range of 1.7-4.3V, and the results are shown in Table 1. Taking Example 1 as an example, at a current rate of 0.1C, the first coulomb efficiency is 96.57%, and the discharge specific capacity can reach 108.72mAh / g. The results are shown in Table 1. Figure 5 shown.

[0086] Table 1 Battery electrical performance test results corresponding to the positive electrode materials obtained in the examples and comparative examples

[0087] Group First coulombic efficiency (%) Discharge specific capacity (mAh / g) Example 1 96.57 108.72 Example 2 94.21 106.15 Example 3 93.72 105.51 Example 4 93.25 106.24 Comparative Example 1 90.25 94.48 Comparative Example 2 85.25 87.45

[0088] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A method for preparing a carbon-coated iron-based composite phosphate positive electrode material, characterized in that: The following steps are involved: S1. Wet-grinding iron salt, M salt, sodium source, phosphorus source, complexing agent and solvent in a stoichiometric ratio in a sand mill to obtain slurry A; S2, spray drying the slurry A to obtain solid powder B; S3, pre-sintering the solid powder B in an inert atmosphere to obtain a precursor C, grinding the precursor C into powder and then compacting it, and sintering it at a high temperature in an inert atmosphere, and after crushing, obtaining a carbon-coated iron-based composite phosphate positive electrode material; wherein the chemical formula of the iron-based composite phosphate positive electrode material is: Na4[Fe x M 1-x ]3[PO4]2P2O7, wherein M is one or more of Ni, Co, Mn, Mg, Ti, Zn, Cu, and 0<x<1.

2. The method for preparing the carbon-coated iron-based composite phosphate positive electrode material according to claim 1, characterized in that: The complexing agent is one or more of citric acid, ethylenediaminetetraacetic acid, nitrilotriacetic acid, oxalic acid, glucose or sucrose.

3. The method for preparing the carbon-coated iron-based composite phosphate positive electrode material according to claim 1, characterized in that: In the iron-based composite phosphate positive electrode material, the molar ratio of (Fe+M):Na:P is 3:4:4; the molar ratio of (Fe+M) to the complexing agent in the iron-based composite phosphate positive electrode material is 1:(1-5).

4. The method for preparing the carbon-coated iron-based composite phosphate positive electrode material according to claim 1, characterized in that: In step S1, the M salt is one or more of soluble oxalates, acetates, nitrates, etc. containing M; the sodium source includes one or more of sodium phosphate, sodium pyrophosphate, disodium dihydrogen pyrophosphate, sodium carbonate, sodium hydroxide, sodium acetate, sodium nitrate, sodium formate and sodium iodide; the phosphorus source includes one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, pyrophosphoric acid, and sodium pyrophosphate; the solvent is one or more of deionized water, methanol, ethanol, butyric acid, octanol, glycol, isopropanol, acetone, lauryl alcohol, and stearic acid.

5. The method for preparing the carbon-coated iron-based composite phosphate positive electrode material according to claim 1, characterized in that: In step S1, the solid content of the slurry A is 10% to 60%.

6. The method for preparing the carbon-coated iron-based composite phosphate positive electrode material according to claim 1, characterized in that: In step S2, the air inlet temperature of the spray drying process is 200-300°C, and the air outlet temperature of the spray drying process is 60-120°C.

7. The method for preparing the carbon-coated iron-based composite phosphate positive electrode material according to claim 1, characterized in that: In step S3, the pre-sintering is carried out at a heating rate of 1-10°C / min from room temperature to 200-400°C, and the pre-sintering is carried out for 2-10 hours; the high-temperature sintering is carried out at a heating rate of 1-10°C / min from room temperature to 450-650°C, and the sintering time is 4-12 hours.

8. A carbon-coated iron-based composite phosphate positive electrode material prepared by the method for preparing a carbon-coated iron-based composite phosphate positive electrode material as described in any one of claims 1 to 7.

9. A positive electrode sheet, characterized in that: The positive electrode plate includes a current collector and an active layer located on the surface of the current collector, and the active layer includes the carbon-coated iron-based composite phosphate positive electrode material prepared by the preparation method of the carbon-coated iron-based composite phosphate positive electrode material described in any one of claims 1-7 or the carbon-coated iron-based composite phosphate positive electrode material described in claim 8.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Method for preparing high capacity lithium iron phosphate cathode material by double sintering

    CN102237520A

  • Method for preparing Na4Fe3 (PO4) 2 (P2O7) by homogeneous phase method and application

    CN113060713A

  • Iron-based composite phosphate positive electrode material, preparation method thereof, positive plate and sodium ion battery

    CN114597385A

  • Carbon-coated sodium-rich sodium ferric pyrophosphate composite positive electrode material, preparation method and application

    CN116169264A

  • Sodium-rich sodium ferric phosphate positive electrode material and preparation method and application thereof

    CN116332144A